The Intersection of Educational Philosophy, Theory, and Curriculum: A Systematic Literature Review and Bibliometric Analysis - Oktarianto, M. Luthfi; Akbar, Sa'dun; Persada, Yuris Indria (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Understanding the intricate intersection of educational philosophy, educational theory, and curriculum development is paramount for advancing pedagogical practice. However, the research landscape on this nexus is complex. This study employs a systematic literature review (SLR) combined with a bibliometric analysis to comprehensively map the intellectual structure, research trends, and thematic concentrations within this specific domain. Following the PRISMA framework , a systematic search was conducted on the Scopus database using the keywords "philosophy of education," "educational theory," and "curriculum development". An initial 6,283 documents were screened based on predefined criteria, resulting in a final corpus of 22 articles for analysis. Bibliometric analysis was performed using VOSViewer to map collaboration networks and keyword co-occurrence patterns. The findings reveal a field marked by renewed, albeit fluctuating, scholarly engagement, with notable publication peaks in 2016 and 2024. The research landscape is geographically concentrated in the United Kingdom and the United States , which form two distinct, non-collaborating transatlantic networks. Despite this, the field is highly fragmented, showing a lack of dominant authors or institutional strongholds. Thematic analysis identifies "Curriculum Development" and "Educational Theory" as the central intellectual pillars, bridging thematic clusters related to "Academic Achievement" and "Professional Competence". The study concludes that this nexus remains a significant research area and highlights a pressing need for future research to foster broader international collaboration and investigate the integration of curricula designed for both academic achievement and professional competence.